2022
DOI: 10.3390/ijerph192013000
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Experiences of Midwives Working in the UK across Three Phases during COVID-19: A Cross-Sectional Study

Abstract: Maternity services cannot be postponed due to the nature of this service, however, the pandemic resulted in wide-ranging and significant changes to working practices and services. This paper aims to describe UK midwives’ experiences of working during the COVID-19 pandemic. This study forms part of a larger multiple phase research project using a cross-sectional design based on an online survey. The online survey used validated psychometric tools to measure work-related quality of life, wellbeing, coping, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Another study from the Netherlands and Belgium revealed that having children was found to be positively related to students’ depression level [ 44 ]. Lastly, a qualitative study from United Kingdom demonstrated higher stress among midwives due to compounded workforce pressures during COVID-19 pandemic such as staffing shortages but also difficulties in maintaining a work-life balance [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study from the Netherlands and Belgium revealed that having children was found to be positively related to students’ depression level [ 44 ]. Lastly, a qualitative study from United Kingdom demonstrated higher stress among midwives due to compounded workforce pressures during COVID-19 pandemic such as staffing shortages but also difficulties in maintaining a work-life balance [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the overarching study, specifically Phase 6, will be used to expand recommendations that could inform or update policies and procedures for HSC employers to help promote safe staffing, increase wellbeing, reduce burnout and improve the quality of working life. Previous publications from the wider HSC workforce study have explored earlier phases of the project [44][45][46][47], the impact on social care and social workers [48][49][50], the 'clapping for carers' initiative [51], the impact on health care professionals [52,53] and a comparison of UK social care workers with those in Japan [54], with future research regarding safe staffing levels currently under review.…”
Section: Aim Of Studymentioning
confidence: 99%
“…Recently, a mixed-methods study on midwives in the United Kingdom showed changes in working practices resulting in increased job demands during the pandemic. It also suggested job resources that could help mitigate the negative health consequences on the midwives, such as ensuring adequate access to personal protective equipment as well as the importance of being valued and listened to in the workplace ( McGrory et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%